ERG3 and ERG11 genes are critical for the pathogenesis of Candida albicans during the oral mucosal infection - Zhou, Yujie (Int J Oral Sci, 2018)
The hyphal development of Candida albicans (C. albicans) has been considered as an essential virulent factor for host cell damage. However, the missing link between hyphae and virulence of C. albicans is also been discovered. Here, we identified that the null mutants of ERG3 and ERG11, two key genes in ergosterol biosynthesis pathway, can form typical hyphae but failed to cause the oral mucosal infection in vitro and in vivo for the first time. In particular, the erg3Δ/Δ and erg11Δ/Δ strains co-cultured with epithelial cells significantly reduced the adhesion, damage, and cytokine (interleukin-1α (IL-1α)) production, whereas the invasion was not affected in vitro. Importantly, they were incapable of extensive hyphal invasion, formation of micro-abscesses, and tongue epithelium damage compared to wild type due to the decrease of the colonization and epithelial infection area in a murine oropharyngeal candidiasis model. The fluconazole (FLC), an antifungal targeted at ergosterol biosynthesis, relieved the epithelial infection of C. albicansin vitro and in vivo even under non-growth inhibitory dosage confirming the virulent contribution of ergosterol biosynthesis pathway. The erg3Δ/Δ and erg11Δ/Δ strains were cleared by macrophages similar to wild type, whereas their virulence factors including agglutinin-like sequence 1 (Als1), secreted aspartyl proteinase 6 (Sap6), and hyphal wall protein-1 (Hwp1) were significantly reduced indicated that the non-toxicity might not result from the change on immune tolerance but the defective virulence. The incapacity of erg3Δ/Δ and erg11Δ/Δ in epithelial infection highlights the contribution of ergosterol biosynthesis pathway to C. albicans pathogenesis and fluconazole can not only eliminate the fungal pathogens but also reduced their virulence even at low dosage.